On Philippine wage structures: Assessing the empirical value of parametric and nonparametric wage functions - Dacuycuy, Lawrence B. (Animo Repository, 2011)
This paper re-examines parametric wage structures vis-a-vis the nonparametric wage function. Using standard Philippine datasets for labor studies, we look into the relative counterfactual predictive abilities of the Mincerian model and its variants to assess stability of wage structures and provide a definitive answer to the issue on the relevance of the nonparametric wage function. We propose to explore the predictive mean square error (PMSE) to measure the degree to which wage structures have changed. Based on the results, we believe that the nonparametric model is indeed relevant for explaining wage structures.